Health Service Innovation: Integration Of Outpatient Online Registration At RSAU Dr. M. Munir Malang - Nadhya Arie Twungga Dewi Murcahayaning Wulan; Achmad Jaelani Rusdi; Febrisari Putri (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Dr. M. Munir Abdulrachman Saleh Air Force Hospital is a Class D Hospital owned by the Indonesian Air Force located in Pakis, Malang Regency. Electronic Medical Records are currently used as a form of transformation of the health care system in Indonesia. Based on the Minister of Health Regulation No. 24 of 2022, it states that all Health Facilities in Indonesia must organize Electronic Medical Records no later than December 2023. However, the use of Electronic Medical Records has not been widespread in health facilities in Indonesia. So, the purpose of this research is to develop an online Dr. M. Munir Abdulrachman Saleh Air Force Hospital outpatient registration application. This research uses a qualitative descriptive method and data collection using observation and interview methods with one of the medical record officers at Dr. M. Munir Abdulrachman Saleh Air Force Hospital. From the results of the study, the design of online registration of outpatients at Dr. M. Munir Abdulrachman Saleh Air Force Hospital to reduce the risk of errors in entering patient data to be registered. The test results show success in use as expected